1996
DOI: 10.1002/(sici)1099-1263(199609)16:5<381::aid-jat355>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ibuprofen and Pentoxifylline in the Treatment of Phosgene-induced Acute Lung Injury

Abstract: Phosgene, a highly reactive former warfare gas, is a deep lung irritant which produces adult respiratory distress syndrome (ARDS)‐like symptoms following inhalation. Death caused by phosgene involves a latent, 6–24‐h, fulminating non‐cardiogenic pulmonary edema. The following dose‐ranging study was designed to determine the efficacy of a non‐steroidal anti‐inflammatory drug, ibuprofen (IBU), and a methylxanthine, pentoxifylline (PTX). These drugs were tested singly and in combination to treat phosgene‐induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 2 publications
1
26
0
Order By: Relevance
“…We have shown that as time increases there is a significant reduction in macrophages and increase in neutrophils in the lavage fluid of mice (Duniho et al, 2001). We have investigated the use of ibuprofen in three different animal models and found that ibuprofen not only reduced the lung wet/dry weight ratio, but also increased survival rates in mice when treatment occurred after exposure (Kennedy et al, 1990;Sciuto et al, 1996b;Sciuto, 1997). The delivery of these agents to exposed individuals should be through inhalation.…”
Section: Discussionsupporting
confidence: 58%
“…We have shown that as time increases there is a significant reduction in macrophages and increase in neutrophils in the lavage fluid of mice (Duniho et al, 2001). We have investigated the use of ibuprofen in three different animal models and found that ibuprofen not only reduced the lung wet/dry weight ratio, but also increased survival rates in mice when treatment occurred after exposure (Kennedy et al, 1990;Sciuto et al, 1996b;Sciuto, 1997). The delivery of these agents to exposed individuals should be through inhalation.…”
Section: Discussionsupporting
confidence: 58%
“…Dosing times were determined based on the t'/a of IBU, which is about 2-4 h, and on previous work done in this laboratory using rats (37). ffiU was mixed in saline 42 mg/ml and pH was adjusted to 7.5 with 300 nl of 0.25 M HCl; the BU was then sterile filtered using a 0.45^ filter cup.…”
Section: Administration Of Ibuprofenmentioning
confidence: 97%
“…Earlier studies, one an isolated perfused rabbit lung and the other, pre/post-treatment administration in rats, focused on the amelioration of phosgene-induced pulmonary edema (37,70). This study focused solely on the survival of mice treated with IBU following a lethal dose of phosgene.…”
Section: Studies With Ibuprofen (Ibu)mentioning
confidence: 99%
“…Dosing times were determined based on the t ½ of IBU, which is about 2-4 h, and on previous work done in this laboratory using rats (Sciuto et al, 1996b). Drug concentrations were determined by the method of Chan, which involved calculations based on the LD50 (Chan et al, 1973).…”
Section: Administration Of Ibuprofenmentioning
confidence: 99%
“…IBU, a cyclooxygenase inhibitor, has been shown to be efficacious in several acute lung injury models such as smoke inhalation (Stewart et al, 1990;Shinoza et al, 1986), paraquat (Lindenschmidt et al, 1983), and acid aspiration (Utsunomiya et al, 1982). IBU has also been examined successfully in previous phosgene inhalation models Sciuto et al, 1996b).…”
mentioning
confidence: 99%